Synthesis of the 21st Century Skills (4C) Based Physics Education Research In Indonesia - Zul Hidayatullah; Insih Wilujeng; Nurhasanah Nurhasanah; Theofilus Gratiamus Gusemanto; Muh. Makhrus (STKIP Singkawang, 2021)
The development of life in the 21st century requires a variety of skills that one must master. Physics learning in schools has a central role in providing 21st-century skills to students. Physics learning is an integrated field that facilitates 21st-century skills and much research is being done in this field. The purpose of this research is to provide a review or general overview related to 21st-century skills-based physics learning research (Communication, Collaboration, Critical Thinking, and Problem Solving, and Creativity and Innovation) in Indonesia. This type of research is a literature study. The articles analyzed are articles published in Sinta-accredited national journals with publication years ranging from 2015-2020 and Scopus indexed international journals, as well as journal research fields focusing on evaluation and learning physics. The number of articles analyzed was 300 articles from national and international journals. From 2015 to 2020, critical thinking skills were the most researched topic with a percentage of 12% and 27% of researchers did not mention the physics topic studied in their research. A lot of learning research, especially physics learning, focuses on a quantitative approach in solving problems in the field of physics education in this case related to 21st-century skills. Most of the 4C skills-based physics learning research uses a relatively small sample of under 100 samples with the majority of the research locations being found mostly focused on Bali-Nusra and Java. The research subjects most frequently researched regarding 21st-century skills are high school level (SMA/SMK/MA).